Comparison Between Overground and Dynamometer Manual Wheelchair Propulsion - Koontz, Alicia M. (J Appl Biomech, 2011)
Laboratory-based simulators afford many advantages for studying physiology and biomechanics; however, they may not perfectly mimic wheelchair propulsion over natural surfaces. The goal of this study was to compare kinetic and temporal parameters between propulsion overground on a tile surface and on a dynamometer. Twenty-four experienced manual wheelchair users propelled at a self-selected speed on smooth, level tile and a dynamometer while kinetic data were collected using an instrumented wheel. A Pearson correlation test was used to examine the relationship between propulsion variables obtained on the dynamometer and the overground condition. Ensemble resultant force and moment curves were compared using cross-correlation and qualitative analysis of curve shape. User biomechanics were correlated (R ranging from 0.41 to 0.83) between surfaces. Overall, findings suggest that although the dynamometer does not perfectly emulate overground propulsion, wheelchair users were consistent with the direction and amount of force applied, the time peak force was reached, push angle, and their stroke frequency between conditions.